MENINGKATKAN EFEKTIVITAS KONDENSOR VERTIKAL PIPA HELIKAL KOIL UNTUK DESTILASI MINYAK ATSIRI SEREH - Nicolas Titahelu; Danny Samuel Pelupessy; Cendy Sophia Edwina Tupamahu; Ammar F Rumagutawan (Jurnal Rekayasa Mesin, 2023)
The main focus of this research is to modify the straight pipe of the Citronella essential oil distillation condenser using a helical coil pipe to shorten the distillation time. This study aims to obtain an effective shell-side fluid volumetric rate to shorten the distillation time. The volumetric rate of the shell side fluid varies from 0.72 to 3.66 LPM at a constant pitch ratio of 2.10. Recording of data in the form of temperature, volumetric rate of shell side water, and tube side steam after steady state is reached. The experimental results show that the effectiveness increases with the increase in the volumetric flow rate of the shell side fluid, where the maximum effectiveness at the volumetric flow rate of 3.66 LPM is 69.99%, while the minimum effectiveness at the volumetric flow rate of 0.72 LPM is 44.39%. The results of the validation of the effectiveness of the condenser show a trend curve that is identical to the previous research, with an average deviation of 5.67%. The maximum volumetric flow rate with a minimum distillation time of 120 minutes with a condensate volume of 8 ml or 240 minutes is smaller than the result of straight-pipe condenser distillation by UKM. The maximum effectiveness is due to an increase in the Reynolds number on the shell side, which results in an increase in the actual heat transfer. It can be concluded that the maximum condenser effectiveness at a maximum volumetric rate of 3.66 LPM could be used for refining Citronella essential oil by SMEs.